Biosynthesis of Vitamin C by Yeast Leads to Increased Stress Resistance - Branduardi, Paola; Fossati, Tiziana; Sauer, Michael; Pagani, Roberto; Mattanovich, Diethard; Porro, Danilo (PloS one, 2007)
In industrial large scale bio-reactions micro-organisms are generally exposed to a variety of environmental stresses, which might be detrimental for growth and productivity. Reactive oxygen species (ROS) play a key role among the common stress factors--directly--through incomplete reduction of O(2) during respiration, or indirectly--caused by other stressing factors. Vitamin C or L-ascorbic acid acts as a scavenger of ROS, thereby potentially protecting cells from harmful oxidative products. While most eukaryotes synthesize ascorbic acid, yeast cells produce erythro-ascorbic acid instead. The actual importance of this antioxidant substance for the yeast is still a subject of scientific debate. We set out to enable Saccharomyces cerevisiae cells to produce ascorbic acid intracellularly to protect the cells from detrimental effects of environmental stresses. We report for the first time the biosynthesis of L-ascorbic acid from D-glucose by metabolically engineered yeast cells. The amount of L-ascorbic acid produced leads to an improved robustness of the recombinant cells when they are subjected to stress conditions as often met during industrial fermentations. Not only resistance against oxidative agents as H(2)O(2) is increased, but also the tolerance to low pH and weak organic acids at low pH is increased. This platform provides a new tool whose commercial applications may have a substantial impact on bio-industrial production of Vitamin C. Furthermore, we propose S. cerevisiae cells endogenously producing vitamin C as a cellular model to study the genesis/protection of ROS as well as genotoxicity.